PROPERTIES OF INNOVATIVE WATER- AND DUST-REPELLENT FABRICS AND LEATHER TREATED WITH ORGANO-SILICONE COMPOUND - Usanova, Farzona; Asomiddinov, Elbek; Sharifova, Lola (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article explores technologies for rendering textiles and leather water- and dust-repellent as well as flame-retardant using organosilicon compounds. Organosilicon compounds, such as polydimethylsiloxane (PDMS), form a thin yet durable hydrophobic and flame-resistant coating on the surface of textiles and leather. This coating significantly reduces the material’s water absorption capacity and lowers its flammability risk. The article analyzes the effectiveness, environmental safety, and economic aspects of treatment with organosilicon compounds. As a scientific novelty, newly developed treatment methods based on organosilicon compounds and their effects on textile and leather properties are presented.